SIGNIFICANCE OF ION INDUCED LUMINESCENCE FOR RADIATION INDUCED BYSTANDER EFFECTS - Ahmad, Bilal Syed (My University, 2013)
Radiation induced bystander effects have given the cancer risk analysis a whole new paradigm. However the actual mechanism involved in producing the effects is still not clear. The basic bystander signal is assumed to be a biological signal. In this study we proposed and tried to quantify the presence of a physical signal in the form of electromagnetic radiation that can trigger a biological response in the bystander cells. In bystander effect studies where the cells are exposed to very low fluence of charged particles there could be several regions that can produce electromagnetic radiation due to the process of atomic/molecular excitations and relaxations. We focused on quantifying the number of ultraviolet photons emitted when charged particles pass through different media that have relevance to radiation biology experiments. The choice of UV photons was made due to the reason that its effects on living cells are very well documented. For this purpose we developed a system which employed the technique of single photon counting to measure the light emitted from samples irradiated under vacuum by a charged particle beam. Photon counting was done using a fast photomultiplier tube (Hamamatsu R7400p) with a peak cathode response at 420 nm wavelength.
In the early set of “proof of principle experiments” we tested polystyrene targets for ion beam induced luminescence. Polystyrene is one of the materials that are used as a cell substrate for radiation biology experiments. The luminescence yield from polystyrene was measured in terms of absolute value i.e. number of photons per second per unit solid angle. The output appeared to have a non-linear behavior with the incident Ion fluence: it rose exponentially to an asymptotic value. We irradiated the samples with beam energies varying from 1 MeV to 2.0 MeV and showed saturation at or before an incident fluence rate of 3×1013 H+/cm2s. The average saturation value for the photon output was found to be 40 × 106 cps. Some measurements were performed using filters to study the emission at specific wavelengths. In the case of filtered light measurements, the photon output was found to saturate at 28×103, 10×106, and 35×106 cps for wavelengths of 280±5 nm, 320±5 nm and 340±5 nm respectively. Using the IBIL signal evolution characteristics with the ion fluence we determined the ions produce a damage having a cross section of the order of 10-14 cm2 in polystyrene. The average radiant intensity was found to increase at wavelengths of 280 nm and 320 nm when the proton energy was increased. Having found an evidence of a significant production of UV in ion irradiated, biologically relevant, material we extended this study further into the measurements from other relevant materials in radiation biology.
Here charged particle irradiation was performed using positively charged protons (H+) ranging in energy from 1.2 MeV to 2.2 MeV at a fluence rate of 2.7×1010 protons mm-2s-1.The materials chosen for this study were polypropylene, Mylar, Teflon, and Cellophane as they are all materials commonly used in radiation biology experiments as cell substrates or containers. In addition, we performed measurements of two NIST standard materials derived from living cells: oyster tissue and citrus leaves. These materials were measured as a powder.
All the container materials were found to emit UV frequency photons at emission levels that are significant enough to warrant further investigation of the potential biological consequences. In addition, the NIST standard reference materials oyster tissue and citrus leaves also emitted UV when irradiated. This suggested that biological materials may themselves emit UV at significant levels when irradiated with charged particles.
We established this further by irradiated cells with β-particles. Cells were plated in Petri-dishes of two different sizes, having different thicknesses of polystyrene (PS) substrate. Exposure of the cell substrates (polystyrene) only resulted in the production of 1035 photons per unit activity in μCi of 90Y which was equivalent to an exposure of 840 β-particles/cm2 to the substrate. For a collimated electron beam exposure, we observed 158-167 photons per unit μCi (18 β-particles per cm2 on the substrate) for different thicknessesof the substrate. Upon irradiating HPV-G cells plated on the PS dishes we determined that the luminescence gradually increased with the increasing exposure of β-particles; reaching up to 250 % of that of the luminescence without any cells for an activity of 180 μCi. For general irradiation conditions we found statistically significant difference in luminescence output for varying cellular densities with cells only and with the application of medium on top of the cells. The colourless medium increased the total luminescence yield while the coloured medium decreased it. When the cells were irradiated using a collimated beam of electrons it was found that the luminescence decreases with the increasing cellular density thus providing an evidence of re-absorption of photons within the surroundings.
After establishing the fact that charged particles induce light emission from the materials that have a relevance to the radiation biology experiments. We extended our study further to find out other sources of radiation that could affect the dose distribution in radiation biology experiments. In radiation biology experiments the low doses of radiation are usually delivered usingamicrobeam charged particle accelerator. Microbeams delivers a highly localized and small dose to the biological medium by using a set of collimators that confine the charged particle beam to a very narrow (micron level) region. Since the collimation block a significant proportion of the beam therefore there is a chance of the production of low energy x-rays and secondary electrons. We used Monte Carlo simulations to investigate the production of particle induced x-rays and secondary electrons in the collimation system and its possible effects on the final dose delivery to the biological medium. We found no evidence of the escape of x-rays or secondary electrons from the collimation system for proton energies of up to 3 MeV. The thickness of the collimators was sufficient to reabsorb all the generated low energy x-rays and secondary electrons. However if the proton energy exceeds 3 MeV then a significant proportion of 10 keV and 59 keV (K-α) x-rays can be emitted by the collimator. Further it was established that due to the phase space distribution of particles in various orientations with the beam axis there are significant chances of hitting non-targetted cells in microbeams that employ a collimator to confine the beam.This may happen due to the beam particles travelling obliquely with the beam axis thus passing the collimator edge and hitting the non-targetted cells. Another reason could be the scatter of beam particles inside the collimator.
The evidence of the production of UV in materials relevant to the radiation biology experiments suggest that the conclusions and hypotheses derived from some radiation bystander experiments need to be re-thought, as charged particle irradiation leads to some level of UV emission in experimental materials which may be the cause of some “non-targeted” effects.
Keywords: Luminescence; UV; Bystander effects; Microbeams; PIXE; Other Physics; Other Physics